Designing a Teaching-Learning Based on Landamatics in Computer Architecture and Its Effect in Achievement (مجلة ديالى للبحوث الانسانية, 2022)
Computer architecture is important and difficult subject in computer department, so it needs always to learn and teach it carefully and in more interest. This is because computer architecture deals with software and hardware, and it needs theoretical and practical aspects.